Boosting Perceptions of the Benefits of Complication Prevention in Reproductive Age Diabetes Mellitus Patients via Self-Talk Affirmation Intervention - Vita Nurlatif (Oshada, 2024)
Diabetes mellitus is a chronic disease that lasts a long time and requires high adherence and self-discipline to carry out comprehensive self-care management to control blood glucose levels and prevent further complications. The practice of self-management requires knowledge or literacy and a positive mindset that is supported by good self-confidence for DM sufferers to be able to do it. Several studies have only examined aspects of physical intervention, such as providing physical activity (DM gymnastics) and education on medication adherence, but there are still few interventions that provide mindset strengthening in the form of self-talk affirmations in order to form a positive perspective on the perception of the benefits of preventing DM complications in sufferers. The study's objective was to ascertain whether using self-talk affirmations would improve DM patients' perceptions of the benefits of preventing complications in Pekalongan Regency, Central Java, Indonesia. 158 individuals with DM participated in this study using a cross-sectional quantitative research approach and a pre-post test sample design. A questionnaire was utilized for data collection, and a Paired T-test for data analysis, which assessed patients' perceptions of the benefits of preventing DM complications either before and after receiving affirmative self-talk therapies. Patients' perceptions of the benefits of preventing DM complications are influenced by the results of self-talk and self-affirmation interventions; there is a difference in the mean score of perceived benefits before and after the intervention. For patients with DM who are of working age, self-talk affirmations might be included to a list of self-management interventions.